Factors affecting demand for money in Japan / Norhidayu Rosli, Norsiah Kadir, Sabri Nayan and Norasyikin Abdullah Fahami - Kadir, Norsiah; Nayan, Sabri; Abdullah Fahami, Norasyikin (Faculty of Business Management, 2013)
Demand for money is considered as an important function of stabilization and structural adjustment policies where such policies depend on the ability to adjust the money supply to its demand in order to prevent monetary disturbances from affecting real output. Monthly data from 2005 to 2012 for various monetary aggregates, consumer price index, industrial production index, and Bond are analysed. Global economic crisis and natural disaster as additional variables have been included in this study. The Pearson correlation tests, Unit root tests, Ordinary Least Square method and Granger Causality tests have been tested for empirical analysis. The results show the existence of the relationship among variables. Bidirectional causality found from CPI and Bond to monetary. All the five variables are significantly affecting the money demand in Japan